A novel inflammatory biomarker in assessing disease activity in ulcerative colitis: gasdermin D - Osman Cagin Buldukoglu; Serkan Ocal; Serdar Akca; Galip Egemen Atar; Besir Kaya; Muhammet Devran Isik; Ozlem Koca; Ferda Akbay Harmandar; Yesim Cekin; Ayhan Hilmi Cekin (BMC Gastroenterology)
Abstract Background Ulcerative colitis (UC) is a chronic inflammatory disease with a worldwide prevalance of around 5 million patients. Assessment of disease activity is crucial in management of UC patients. Gasdermin D (GSDMD) is a protein which belongs to the gasdermin protein family and plays a role in inflammatory cell death, pyroptosis. GSDMD activation has been shown to be related to inflammatory states in a variety of disorders, including inflammatory bowel diseases. With this study, we aimed to reveal a potential new inflammatory serum marker for assessing disease activity and severity in UC patients in a non-invasive manner. Materials and Methods This prospective study was carried out at Antalya Training and Research Hospital, Turkey, between September 2022 and March 2024. 93 UC patients were enrolled in the study. Patient and disease characteristics, laboratory workout data, and severity indexes comprising Truelove and Witts’ severity index (TWSI) and Mayo endoscopic subscore (MES) were analyzed with serum GSDMD levels. Results GSDMD, CRP (C-reactive protein), and body-mass index were statistically significant independent predictors of increasing disease severity according to TWSI. GSDMD and CRP were statistically significant independent predictors of higher MES scores. GSDMD demonstrated excellent discriminative performance in distinguishing patients with moderate-to-severe MES from those with normal or mild MES, with an area under the curve value of 0.976. A cut-off value of 6.0 ng/mL for GSDMD was identified as optimal, yielding a sensitivity of 95.0%, a specificity of 86.3%, and a Youden Index of 0.813. Conclusion The results of the study revealed that GSDMD is a robust biomarker in predicting a more severe disease state for UC in terms of TWSI and MES, putting this novel protein into highlight as a potential new biomarker in patients with UC.